Avaliação da prevalência e caracterização da rinossinusite nos cuidados de saúde primários em Portugal - Barros, E (2012)
Abstract: To determine RS prevalence, diagnosed at the Portuguese Primary Health Care Centres (PHCC), and to assess diagnostic and treatment practices. Study Design: Epidemiologic, cross-sectional study. Material and Methods:A cohort of subjects attending general practice medical appointments, in selected PHCC, was evaluated. Results: Between May/2008 and June/2009, 1,201 subjects were included with a mean age of 41.7+13.2 years, of which 71% were female. The total prevalence of RS was 19.2%, [n=231; 17.1%, 21.5%; 95% CI]. The prevalence of acute RS was 7.4%, [n=89; 6.0%; 9.0%; 95% CI], and of chronic RS was 13.% [n=156; 11.2%, 15.0%; IC 95%]. The estimated prevalence of RS is high. About 92% of patients with RS presented at least one symptom for disease diagnosis (p<0.001). Conclusions: Half the patients (50%) with RS had already been submitted to, at least, one medical exam. Same relevant difference between RS diagnostic and treatment guidelines and the current practice in Primary Health Care Centres were found.